Temporal patterns in coral reef fish assemblages with varying disturbance levels: A tale of two National Parks in Hawai´i - Fukunaga, Atsuko; McKenna, Sheila A.; Brown, Eric K.; McCutcheon, Amanda L.; Burns, John H. R. (Frontiers in Marine Science, 2022)
Long-term ecological monitoring of coral reefs can reveal the state of the reef communities and responses of different reef components to various pulse and press disturbance events. Here, we describe long-term monitoring of reef fish assemblages from two U.S. National Parks in Hawai‘i, Kaloko-Honokōhau National Historical Park (KAHO) and Kalaupapa National Historical Park (KALA) over the past decade. These two parks experience different anthropogenic disturbances as KAHO is highly accessible with multiple types of adjacent land use while KALA is relatively inaccessible, surrounded by large expanses of native forest, and known for having the highest documented fish biomass within the main Hawaiian Islands. The fish assemblages in KAHO were numerically dominated by small-bodied damselfish Chromis spp. and herbivorous surgeonfishes Acanthurus nigrofuscus, Ctenochaetus strigosus and Zebrasoma flavescens, while those in KALA were numerically dominated by Chromis vanderbilti, A. nigrofuscus, Thalassoma duperrey and Paracirrhites arcatus. Multivariate control charts detected anomalies in the fish assemblages in some years. In KAHO, gradual shifts in the assemblages were detected in recent years due to changes (both increases and decreases) in relative abundances of numerically dominant species including Chromis agilis, C. vanderbilti, A. nigrofuscus, C. strigosus and Z. flavescens. There was a documented reduction in live coral cover in KAHO due to a bleaching event in 2015, and potential delayed effects of the coral mortality on the fish assemblages were found particularly in the North and South regions of the park. In KALA, increases in the abundances of Acanthurus (A. blochii, A. leucopareius, A. nigrofuscus, A. thompsoni and A. triostegus) and C. strigosus were found in 2014, likely due to a large recruitment event that had not been well reported. As localized thermal stress events were detected in both KAHO and KALA in 2019, continuous monitoring of these two parks is critical to assess how the coral-reef ecosystems under two different human-use scenarios respond to repeated heating events and whether there are immediate as well as delayed effects on reef organisms resulting from losses of live coral tissue and a subsequent decrease in structural complexity provided by the coral.